The assessment of intellectual capital: a measurement model and empirical study of the structure and relationship of capital elements - A. B. Kashkinbayev; G. N. Jaxybekova (Экономика: стратегия и практика, 2020)
The article discusses the basics of intellectual capital management (IC), IC measurement, which attract much attention of scientists and practitioners. The goal of this work is to research a measurement model and a system of quality IC indices to provide companies with a good tool for managing IC. Based on a review of several measurement models of IC proposed by Western researchers, IC is classified into human capital, structural capital, innovation capital and consumer capital, and then based on the analysis of their content, a system of qualitative indices for the above four elements of IC is developed. As a result of an empirical study, it was found that there is a significant relationship between the scores of the four elements of the company’s IC and its business indicators, which proves the validity and rationality of the IC measurement model and the system of quality indices. At the same time, empirical research once again proves that there is a good relationship between the four elements of IC. Therefore, enterprises should manage their IC and improve them from an integrative point of view.